Size Dependent Optical Nonlinearity and Optical Limiting Properties of Water Soluble CdSe Quantum Dots. (26th November 2014) - Augustine, Anju K.; Mathew, S.; Radhakrishnan, P.; Nampoori, V. P. N.; Kailasnath, M.
Abstract : We present third-order optical nonlinear absorption in CdSe quantum dots (QDs) with particle sizes in the range of 4.16–5.25 nm which has been evaluated by theZ -scan technique. At an excitation irradiance of 0.54 GW/cm 2 the CdSe QDs exhibit reverse saturation indicating a clear nonlinear behavior. Nonlinearity increases with particle size in CdSe QDs within the range of our investigations which in turn depends on the optical band gap. The optical limiting threshold of the QDs varies from 0.35 GW/cm 2 to 0.57 GW/cm 2 which makes CdSe QDs a promising candidate for reverse-saturable absorption based devices at high laser intensities such as optical limiters.